2020
DOI: 10.3390/cells9040893
|View full text |Cite
|
Sign up to set email alerts
|

Key Components of Human Myofibre Denervation and Neuromuscular Junction Stability are Modulated by Age and Exercise

Abstract: The decline in muscle mass and function with age is partly caused by a loss of muscle fibres through denervation. The purpose of this study was to investigate the potential of exercise to influence molecular targets involved in neuromuscular junction (NMJ) stability in healthy elderly individuals. Participants from two studies (one group of 12 young and 12 elderly females and another group of 25 elderly males) performed a unilateral bout of resistance exercise. Muscle biopsies were collected at 4.5 h and up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(63 citation statements)
references
References 41 publications
9
54
0
Order By: Relevance
“…Indeed it is possible that muscle damage is the main driver of the macrophage response. However, we detected similar increases in circulating creatine kinase in the young and elderly females at 5 days post exercise, together with similar numbers of fibers positive for neonatal myosin at this time point (Bechshøft et al, 2019;Soendenbroe et al, 2020) suggesting that muscle damage leading to necrosis was absent. This is further supported by the complete lack of fibers containing macrophages in the present study.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Indeed it is possible that muscle damage is the main driver of the macrophage response. However, we detected similar increases in circulating creatine kinase in the young and elderly females at 5 days post exercise, together with similar numbers of fibers positive for neonatal myosin at this time point (Bechshøft et al, 2019;Soendenbroe et al, 2020) suggesting that muscle damage leading to necrosis was absent. This is further supported by the complete lack of fibers containing macrophages in the present study.…”
Section: Discussionsupporting
confidence: 54%
“…This study is based on muscle biopsy analyses from two studies, one on 25 elderly men (Heisterberg et al, 2018) and one on 12 young and 12 elderly women (Bechshøft et al, 2019;Soendenbroe et al, 2020). Both studies were approved by The Committees on Health Research Ethics for The Capital Region of Denmark (Ref: H-15017223, H-3-2012-081).…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…After further screening of remaining articles, 49 were excluded, in which 23 had no comparisons among different ages, 20 were review papers 4 were conference reports and 2 had no full text access. Therefore, 30 manuscripts were included for the systematic review (Courtney and Steinbach, 1981;Banker et al, 1983;Oda, 1984;Herscovich and Gershon, 1987;Smith and Chapman, 1987;Anis and Robbins, 1988;Smith et al, 1990;Prakash and Sieck, 1998;Connor et al, 2002;Deschenes and Wilson, 2003;Apel et al, 2009;Mcmullen and Andrade, 2009;Suzuki et al, 2009;Kulakowski et al, 2011;Li et al, 2011;Samuel et al, 2012;Cheng et al, 2013;Deschenes et al, 2013;Personius and Parker, 2013;Aare et al, 2016;Willadt et al, 2016;Xie et al, 2016Xie et al, , 2018Hughes et al, 2017;Liu et al, 2017;Snyder-Warwick et al, 2018;Zhao et al, 2018;Soendenbroe et al, 2019Soendenbroe et al, , 2020Uchitomi et al, 2019). The flow chart presenting the selection process is shown in Figure 1.…”
Section: Results Of the Searchmentioning
confidence: 99%
“…The study by Soendenbroe et al, supported the role of exercise in maintaining NMJ stability, even in elderly inactive individuals [18], whereas Jin and co-workers demonstrated that the functions of Lysine (Lys), the first limiting essential amino acid for mammals, in muscle mass accumulation are mediated by satellite cells and the mTORC1 pathway [19].…”
mentioning
confidence: 99%